2013
DOI: 10.1111/and.12130
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective effect ofl-carnitine on motility, vitality and DNA oxidation of human spermatozoa

Abstract: Successful cryopreservation for human spermatozoa markedly influences the reproductive outcomes of assisted reproductive technologies. But in spite of its usefulness, cryopreservation significantly decreases sperm quality. l-carnitine has been found to improve the quality of spermatozoa in selected cases with male infertility. Here, we examined the efficacy of l-carnitine in improving sperm motility and vitality and reducing sperm DNA oxidation during cryopreservation. Semen samples from infertile patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 22 publications
6
61
1
2
Order By: Relevance
“…In conclusion, although many studies have shown the effect of L-carnitine in common infertility (Trasler and Robaire, 1988;Moradi et al, 2010;Banihani et al, 2014), there are no studies of L-carnitine in relation to CP-induced infertility. Our results, for the first time, have shown a promising effect and one of its possible mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…In conclusion, although many studies have shown the effect of L-carnitine in common infertility (Trasler and Robaire, 1988;Moradi et al, 2010;Banihani et al, 2014), there are no studies of L-carnitine in relation to CP-induced infertility. Our results, for the first time, have shown a promising effect and one of its possible mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…One obvious mechanism is that metformin reduces the level of oxidative stress (Banihani et al, 2014), an imbalance between oxidants and antioxidants to the favor of the former, and lipid peroxidation (Attia, Helal, Alhaider, 2009). It has been shown that metformin supplementation at 30 mg/kg restores the antioxidant function such as reduced glutathione, superoxide dismutase, catalase, glutathione peroxidase, and glutathione-S-transferase in diabetic male rats (Adaramoye, Lawal, 2014).…”
Section: Positive Effectsmentioning
confidence: 99%
“…Combination therapy with L-carnitine (2g/day) and acetyl-L-carnitine (500mg twice a day) is also effective in improving sperm quality in infertile patients (Lenzi et al, 2004) [66,67] and it improves the total oxyradical scavenging capacity of the seminal fluid [68] and sperm parameters [68]. Interestingly, the addition of L-carnitine in samples to be cryopreservation improves significantly sperm quality [70].…”
Section: Carnitinementioning
confidence: 99%